Desenhos que ensinam sobre o passado: a aplicabilidade das histórias em quadrinhos (hqs) no ensino de história - Costa, Jonathan Diógenes (2019)
History has been written and reframed, especially after the outbreak of the Annales influence. The problematization of the most diverse sources led to the raising of new perspectives on the field of historiographical research and the teaching of history. Among the emerging universe of visual culture, Comics (Comic Book) represents an ingenious source for the fabric of history taught. Given this scenario, this paper aims to investigate the applicability of comic books in History Teaching, based on the theoretical studies of Eisner, Vergueiro, Palhares, Vilela, Circe Bittencourt and Maria Auxiliadora Schmitt. The text is structured in two broad strands: firstly, it deals with the evolution of comic books and then their applicability in teaching in the classroom. It also contemplates a historiographical course of the discipline of History and the emergence of new sources of research and teaching, where the comic finds its captive place. Then, by analyzing the images of three comic books - D. João Carioca: The Portuguese Court in Brazil (1808-1821); Brazilian History in Comics and The Fight against Canudos - addresses the applicability of visual culture in teaching, without forgetting the reflections that sharpen the critical sense of students in the classroom, to form student-citizens committed to the realities that surround them.